Drug addictions and sexual violence in childhood and adolescence: analyzing life stories - Doescher, Andréa Marques Leão [UNESP]; Leão, Andreza Marques de Castro [UNESP]; Ribeiro, Paulo Rennes Marçal [UNESP] (My University, 2014)
The sexual abuse suffered in childhood and adolescence, in addition to damage to physical and psychological health of the victim, is considered as an important risk factor for alcohol and drugs addiction, development of psychopathology and psychosocial damage in adulthood. In addition to the pain and humiliation that are submitted by the abuse, children and adolescents also experience shame and guilt which require them to adopt coping strategies to endure those feelings. The use of psychoactive substances is a recognized way of dealing with the pains of living. This work, which is of narrative style, analyses and discusses, through five case reports, chemical dependency as a result of sexual abuse suffered in childhood and/or adolescence. The eight subjects in this study are male and have suffered sexual violence in this age period of life. Their ages range from 23 years to 39 years, and all are admitted to a therapeutic community in a city in the interior of Sao Paulo state, in Brazil, for treatment of chemical dependency, being met by the Department of Psychology. The reasons for the choice of the participants for treatment modality for patients are: difficult to stop using drugs, even unwilling to take it, they have easy access to it; the feeling of losing control over their lives; by successive losses as a result of drug use, and for fear that their lives had a tragic ending. With the exception of two participants, the others do not classify that as a child suffered sexual violence. However, all attribute that facilitated their entry into the world of drugs. Seven participants experienced such violence in childhood (between 7 years and 9 years) and adolescence (age 14). The attackers were people closed to the victims—in the case of two victims, their families, with the exception of one participant who was raped by a stranger. Six participants declared themselves as homosexual. Another participant does not claim to be homosexual, but presents difficulties in terms of sexuality. Two participants are HIV positive. The start of psychoactive substances use occurred during adolescence (12 years to 17 years). The participants see drugs as an anesthetic to the pain of the soul, a way to get pleasure, but they get charged expensively, as it increases the feeling of emptiness, guilt, helplessness, worthlessness and hopelessness. Although participants have sought help to deal with addiction, it is noted that throughout the life course the issue of sexual violence was not treated. It was noted that the patients have a double stigma in society: the issue of drugs addiction and the orientation of sexual desire, because the majority of participants are homosexual. The results reinforce the need for effective action geared to accommodate the victims of sexual violence and effective preventive measures to prevent children and adolescents from being abused.
Keywords: Sexual violence; Childhood and adolescence; Male gender; Chemical dependency; Sexuality